PRUEBA DE DIFERENTES FUNGICIDAS PARA EL CONTROL DEL CHAMUSCO DEL PLATANO - RODRIGUEZ BAEZ, ROBERTO (My University, 1959)
no
CAMPO
Keywords: PRUEBA, DIFERENTES, FUNGICIDAS, CONTROL, CHAMUSCO, PLATANO; CIENCIAS AGRARIAS; AGROQUIMICA; FUNGICIDAS